An evaluation of the technique of use of metered dose inhaler administration in bronchial asthma children - Makarani, Mustak M.; Patel, Prakruti P.; Gandhi, Anuradha M.; Desai, Chetna K.; Desai, Mira K. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Inadequate understanding and performance of drug administration using metered-dose inhaler (MDI) in paediatric population affects therapeutic outcome. Hence, this study aimed to evaluate the impact of two educational interventional methods for usage of MDI in paediatric patients of bronchial asthma. Methods: This prospective, interventional study was done in paediatric asthma patients who were prescribed drugs with (MDI) with/without spacer at outpatient department of pediatrics. Patients were divided in group A (video) or group B (leaflet) as per random table method and method to use MDI was assessed by using checklist as per WHO guide to good prescribing at baseline. Investigator taught the technique by a video (group A) and leaflet (group B) to the selected population. Patients were followed up after 15 days and assessed for use of MDI using the same checklist. Data were analysed by using paired and unpaired ‘t’-test. Results: A total of 100 pediatric asthma patients were included in study group A (50) and group B (50). The average no. of steps (WHO checklist) followed was significantly improved at post intervention in both group A (with spacer, p<0.0001) as well as B (without spacer, p<0.05). Although average no. of steps followed were more in group A, no significant difference was found between two groups after intervention. Conclusions: As video is an audio-visual method of demonstration, and hence help us memorise the step of inhalational technique in pediatric patients. Repeated demonstration/education to patients/caregivers may improve the method of MDI usage.